Usability and Utilization of ICT Among Educational Administrators in Secondary Students in Public School - H. O. Bolaji; Hassanat Abdullateef Jimoh (Indonesian Journal of Educational Research and Technology, 2023)
This study examines the usability and utilization of ICT difficulty among educational administrators in secondary students in public schools, Kwara state, Nigeria. Despite the roles of ICT can play in education, secondary schools in Nigeria are yet to comprehensively adapt them for teaching and learning. Efforts geared towards the integration of ICTs into the secondary school system have not had much impact. The paper identified inadequate funding of ICT education, inadequate ICT facilities in secondary schools, unstable power supply, High Cost of ICT facilities, poor implementation of Government policies on ICT, poor network service and coverage, and poor ICT literacy as the challenges preventing effective administration of ICT in the public secondary schools in Kwara State. The paper thereby suggests the following: government should increase the funding of ICT education, provide capacity development for teachers and school administrators, provide adequate ICT facilities, ensure a constant supply of power and implement all the ICT educational policies. Recommendations were then made to the government.